How Far Math Teachers Evaluate Attitude Students at Vocational School? Studies Phenomenology in Yogyakarta - Astuti, Nuryani Dwi; Hajaroh, Mami; Prihatni, Yuli; Setiawan, Ari; Retnawati, Heri; Suyanto, Slamet; Abd Aziz, Mohd Kasturi Nor (International Journal of Scientific Research and Management (IJSRM), 2025)
Importance evaluation attitude students at School Intermediate Vocational often neglected, though matter This own impact on the development of students and preparation for the world of work. Study This aims to understand to what extent the mathematics teacher evaluates the attitude of students at vocational school. With an approach to phenomenology and involving 16 vocational school teachers in Yogyakarta, the research used a questionnaire open and interview for collecting data. Data analysis shows that math teachers evaluate the attitude of students through five stages, including base evaluation attitude, planning, implementation, obstacles, and suggestions. The findings mainly cover the fact that evaluation attitude is not optimal, more teachers focus on the instrument cognitive, and yet There is an instrument valid and reliable attitude. Need exists attention more to evaluation attitude for increase quality education at vocational schools.